Control interno de la Sociedad TTT-Punto-Mas-Salud S.A.S. de la ciudad de Babahoyo, período 2022. - Ramírez Verdezoto, Carlos Luis (2025)
The purpose of the argument presented in this work is to determine an analysis of internal control in the pharmaceutical company SOCIEDAD TTT-PUNTO-MAS-SALUD S.A.S. of the city of Babahoyo, which allows presenting recommendations that serve as a guide for strengthening its current internal control system. The information compiled and used was acquired through interviews, opinions and questionnaires with officials, which served for the analysis and determination of the company's internal control practices. The study was carried out with the use of questionnaires for the evaluation of internal control components according to the COSO model, in such a way that based on this model, recommendations are provided to improve control within the company, because internal control is fundamental. for the achievement of effectiveness and efficiency in the development of the company's economic activity, which provides policies, processes and procedures that direct all components of the company to achieve the set objectives.